The effect of pulsed electric fields on carotenoids bioaccessibility: The role of tomato matrix. (1st February 2018) - Bot, Francesca; Verkerk, Ruud; Mastwijk, Hennie; Anese, Monica; Fogliano, Vincenzo; Capuano, Edoardo
Highlights: Tomato fractions were subjected to pulsed electric field treatments. Effect of pulsed electric fields on bioaccessibility is structure dependant. In tomato tissue, bioaccessibility was not affected by pulsed electric field. Pulsed electric fields reduced carotenoids bioaccessibility in tomato chromoplasts. Abstract: Tomato fractions were subjected to pulsed electric fields treatment combined or not with heating. Results showed that pulsed electric fields and heating applied in combination or individually induced permeabilization of cell membranes in the tomato fractions. However, no changes in β-carotene and lycopene bioaccessibility were found upon combined and individual pulsed electric fields and heating, except in the following cases: (i) in tissue, a significant decrease in lycopene bioaccessibility upon combined pulsed electric fields and heating and heating only was observed; (ii) in chromoplasts, both β-carotene and lycopene bioaccessibility significantly decreased upon combined pulsed electric fields and heating and pulsed electric fields only. The reduction in carotenoids bioaccessibility was attributed to modification in chromoplasts membrane and carotenoids-protein complexes. Differences in the effects of pulsed electric fields on bioaccessibility among different tomato fractions were related to tomato structure complexity.